(untitled) (Heritage, 2021)
In the period from the end of the 18th century to 1912, being the last period of Turkish rule, the education system was built and completed more slowly than before, and it only partially belonged to the education system of the Ottoman Empire. Schools did not belong to the same school system because Turkish,Serbian and other schools coexisted at the time in Kosovo.Considering a wider and more general picture of the development of literacy in Kosovo and Metohija, it can be concluded that education had its ups and downs, changing periodically depending on social and political conditioning. The school system in Mušutište and Sredskadepicts the chronology of events in the development of the school’s function as an educational institution.Many events and happenings from the history of these schools will remain unknown, but at least, a part of the actions and memories will be torn from oblivion and further systematized into one whole.Therefore, the aim of this paper is to give guidance to future generations encouraging them to deal with the topic more thoroughly, so that one day these villages would serve as an example to other rural schools and urge them to start writing and publishing the history of their schools.Only then will all the values ​​of the stay and survival of Serbs in Mušutište and Sredska be confirmed.The subject discussed in the paper is more important for the spiritual existence of the Serbian people, because it characterizes a continuous struggle for national, economic and cultural identity of the Serbs, the scuffle for national and individual survival, and every detail embodies a valuable effort to persevere in the harsh and despotic conditions of Turkish rule.